PENGGUNAAN PASTA CAP BEBAS MINYAK PADA PENCAPAN KAIN KAPAS DENGAN ZAT WARNA ACRAMINE - Agus Taufiq; Riski Ayu Nurmansyah; Nisrina Qurotu Ain (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
The comfort and absorbency properties of the cotton fiber solution make it widely used both as a standalone raw material and as a mixture with artificial fibers. Likewise in the process of printing, cotton fabrics also play an important role as textile materials are widely used because of better result than other textile materials. Printing cotton fabrics with dye pigments made with pasta cap emulsion containing oil, so that environmental pollution problems will always arise, for that it is necessary to overcome or minimize the risk of environmental pollution as a result of the printing process, using a pasta stamp that is free from petroleum solvents. This study examines the use of oil-free paste stamps on the printing of cotton fabrics with acramine dyes. Paste stamp is made using a synthetic thickener with the amount of thickener usage varies from 5 g, 10 g, 15 g, 20 g and 25 g as well as the temperature variation of the preserved heater by 1300C; 1400C; and 1500C using the dye pigments acramine as much as 20 g with a heater mounted for 3 minutes. The results of the study (with a quality evaluation in terms of aging color and color dispersion) indicates that the greater the amount of thickener used, the color that occurs increasingly older, while higher temperatures The preheated heater relative does not affect the color aging. The optimum results in this study were achieved on the use of thickener of 20 g and the preserved heating temperature of 1500C. When compared with the use of an emulsion paste cap (using an oil solvent), the result of the stamp using a solution-free (systemsolvent-free) solution cap stamp gives a nearly equal and good value.